2009
DOI: 10.1159/000249147
|View full text |Cite
|
Sign up to set email alerts
|

<i>EGR4</i> Is a Master Gene Responsible for Fertility in Cryptorchidism

Abstract: The purpose of early medical or surgical treatment of boys with undescended testes is to prevent the development of infertility. However, early and successful surgery cannot prevent infertility in cryptorchid boys who lack type A dark (Ad) spermatogonia. The aim of this study was to compare the gene expression pattern of patients with completed transformation of gonocytes into Ad spermatogonia, associated with low infertility risk, with patients that had failed to undergo this process and had a high infertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 48 publications
8
58
0
Order By: Relevance
“…Whole genome expression analysis strongly supports the theory that impaired mini-puberty is responsible for azoospermia and adult infertility in cryptorchidism [49]. Multiple differences in gene expression between high- and low-infertility risk groups underscore the importance of an intact hypothalamus-pituitary-testicular axis in fertility development.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Whole genome expression analysis strongly supports the theory that impaired mini-puberty is responsible for azoospermia and adult infertility in cryptorchidism [49]. Multiple differences in gene expression between high- and low-infertility risk groups underscore the importance of an intact hypothalamus-pituitary-testicular axis in fertility development.…”
Section: Resultsmentioning
confidence: 67%
“…Multiple differences in gene expression between high- and low-infertility risk groups underscore the importance of an intact hypothalamus-pituitary-testicular axis in fertility development. Molecular biological observations support LH deficiency, with EGR4 as a master gene over Leydig cell dysgenesis as the reason for impaired mini-puberty [49]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, analyzing the whole genome expression profiling of testicular tissue, we found that cryptorchid boys lacking Ad spermatogonia had decreased expression of most of the genes essential for hypothalamo-pituitary-testicular axis function ( table 1 ). In particular, EGR4 , which is involved in regulating the secretion of luteinizing hormone, was virtually silent in the HAZR group [Hadziselimovic et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…cDNAs were synthesized with the Reverse Transcriptase Core Kit (Eurogentec, cat# RT-RTCK-03) using random primers [Hadziselimovic et al, 2009]. Real-time PCR runs were performed using SYBR Fast Kit (Kapa Biosystems, cat# KK4602) with each gene-specific primer at 200 n M final concentration in a total volume of 17.5 l. Wave lengths for source and detection were set at 470 and 510 nm, respectively.…”
Section: Statistical Analysis and Interpretation Of Microarray Datamentioning
confidence: 99%
“…In those for whom this minipuberty is blunted or non-existent, the risk of being azoospermic in adulthood is high. 12 Hadziselimovic et al 13 has demonstrated that EGR4 is a critical, master gene of sorts responsible for the regulation of LH secretion and, as such, for the initiation of the minipuberty. Therefore, cryptorchidism, either unilateral or bilateral, whether corrected early or later, is an important risk factor for azoospermia.…”
Section: The Medical and Surgical History: What Clues Might It Reveal?mentioning
confidence: 99%